2007
DOI: 10.1111/j.1525-1470.2007.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Curettage Technique for Molluscum Contagiosum

Abstract: Molluscum contagiosum is a frequently occurring, virally induced cutaneous condition that affects infants, children, and adults. Although historically considered a self-limiting entity, many patients experience prolonged infections, often resistant to varied therapeutic interventions. Topical treatments achieve complete clearance in only a limited number of patients. Because of the associated pain, affected children are characteristically uncompliant to commonly used destructive modalities. We describe a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…But, it needs to be performed with adequate anesthesia for optimal results. It is time consuming, and may not be appropriate in a busy office setting (9).…”
Section: Discussionmentioning
confidence: 99%
“…But, it needs to be performed with adequate anesthesia for optimal results. It is time consuming, and may not be appropriate in a busy office setting (9).…”
Section: Discussionmentioning
confidence: 99%
“…Curettage is commonly used to treat MC but is commonly associated with pain and fear 2,4–6 . Among our 102 patients recruited with a clinical diagnosis of MC, six could not be included because of excessive fear before or during the curettage procedure.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 One of the most commonly used therapies is removal with a sharp curette. 2,[4][5][6] In a recent prospective randomized trial, curettage was found to be more efficient and had a lower rate of side-effects than other therapeutic options, i.e. cantharidin, combination of salicylic acid and lactic acid, or imiquimod.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Curettage administered to carefully selected patients can prove beneficial in the treatment of MC lesions. The epithelial surface of the papule is opened with a needle and the viral core is scraped away (sometimes using topical local anesthesia) . Common side effects include pain, bleeding, and infection.…”
Section: Curettagementioning
confidence: 99%